Effect of early enteral nutrition on postoperative nutritional status and immune function in elderly patients with esophageal cancer or cardiac cancer - Yu, Guiping; Chen, Guoqiang; Huang, Bin; Shao, Wenlong; Zeng, Guangqiao (Chinese Journal of Cancer Research; Vol 25, No 3 (June 28, 2013): Chinese Journal of Cancer Research, 2013)
Objective: To explore the effect of early enteral nutrition (EN) on postoperative nutritional status, intestinal permeability, and immune function in elderly patients with esophageal cancer or cardiac cancer. Methods: A total of 96 patients with esophageal cancer or cardiac cancer who underwent surgical treatment in our hospital from June 2007 to December 2010 were enrolled in this study. They were divided into EN group (n=50) and parenteral nutrition (PN) group (n=46) based on the nutrition support modes. The body weight, time to first flatus/defecation, average hospital stay, complications and mortality after the surgery as well as the liver function indicators were recorded and analyzed. Peripheral blood samples were collected on the days 1, 4 and 7 after surgery. The plasma diamine oxidase (DAO) activity and D-lactate level were determined to assess the intestinal permeability. The plasma endotoxin levels were determined using dynamic turbidimetric assay to assess the protective effect of EN on intestinal mucosal barrier. The postoperative blood levels of inflammatory cytokines and immunoglobulins were determined using enzyme-linked immunosorbent assay (ELISA). Results: After the surgery, the time to first flatus/defecation, average hospital stay, and complications were significantly less in the EN group than those in the PN group (P